KUALITAS HIDUP PASIEN GAGAL GINJAL KRONIK TERKOMPLIKASI YANG MENJALANI HEMODIALISA DI RS “X” KOTA SEMARANG - FX Sulistiyanto Wibowo S; Erna Prasetyaningrum (Dian Nuswantoro Semarang, 2022)
Quality of life is a condition where a person gets satisfaction or enjoyment in everyday life. The quality of life concerns physical health and mental health, which means that if a person is physically and mentally healthy, that person will achieve satisfaction in his life. Physical health can be assessed from physical function, physical role limitations, body pain, and perceptions of health. Mental health itself can be assessed from social function and the limitations of the emotional role. In addition, indicators of quality of life include the domain of physical health, the domain of psychological well-being, the domain of social relations, and the domain of relationships and the environment. Chronic kidney failure is in the top 20 causes of death in the world and the top 10 causes of death in Indonesia. Problems that arise due to chronic kidney failure are multi-organ disorders, accumulation of urea, which can cause poisoning, edema, anemia, and a drastic decrease in physical abilities, reducing the patient's quality of life.This research is a type of research conducted as an exploratory descriptive study with a cross-sectional design. This research was carried out at the